2022
DOI: 10.3389/fnut.2022.860575
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ramadan and Non-ramadan Intermittent Fasting on Gut Microbiome

Abstract: BackgroundIn recent years, intermittent fasting (IF) has gained popularity in the health and wellness in the world. There are numerous types of IF, all of which involve fasting periods that last longer than an overnight fast and involve limited meal time-windows, with or without calorie restriction. The objective of this review is to summarize the current evidence for the effects of Ramadan and non-Ramadan IF on gut microbiome.MethodsWe explored PubMed, Scopus, Web of Science, and Google Scholar according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…This landscape view of interconnected dietary behaviors, microbiota, and metabolites contributes to the future development of personalized, diet-based therapeutic strategies for gut-related disorders. Mousavi et al 54 summarized the current evidence for the effects of RF and non-Ramadan IF on the gut microbiome. Animal and human studies were screened and reviewed separately by two researchers.…”
Section: Resultsmentioning
confidence: 99%
“…This landscape view of interconnected dietary behaviors, microbiota, and metabolites contributes to the future development of personalized, diet-based therapeutic strategies for gut-related disorders. Mousavi et al 54 summarized the current evidence for the effects of RF and non-Ramadan IF on the gut microbiome. Animal and human studies were screened and reviewed separately by two researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 27 included reviews, only one systematic review ( 21 ) and a scoping review ( 22 ) evaluated the effects of Orthodox fasting on health/nutritional outcomes. The remainder reviews ( n = 25) focused on the effects of Ramadan fasting on anthropometric and metabolic markers ( 23 25 ), glucometabolic parameters ( 26 29 ), salivary flow rate, inflammatory and metabolic variables ( 30 ), immunity, inflammatory markers and infectious events ( 31 33 ), blood pressure and cardiovascular events ( 34 36 ), liver function ( 37 ), renal function and chronic kidney diseases ( 38 , 39 ), body mass (i.e., body weight) and body composition ( 40 42 ), intestinal microbiome changes ( 43 ), hormones regulating appetite and satiety ( 44 ), psychiatric parameters ( 45 ), sleep quality ( 46 ) and pregnancy outcomes ( 47 ). The characteristics and the main outcomes of the included reviews are presented in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…Some findings have revealed that fasting diets can also cause changes in the microbiome ( 129 , 130 ). In a recent systematic review, Mousavi et al ( 43 ) reported that Ramadan fasting improves health parameters through positive effects on some bacterial strains such as Akkermansia muciniphila and Bacteroide .…”
Section: Religious Fasting Nutrition and Individual Healthmentioning
confidence: 99%
“…Therefore, fasting can impact SCFA concentrations in the blood. The duration of fasting, dietary differences, use of probiotics, and medication could potentially affect our results including differences between patients with MASLD and controls [ 32 34 ]. There is no clear evidence showing the effect of diet or medication on SCFAs but a systematic review found no clear effect of supplementary dietary fibers on SCFA levels [ 34 ].…”
Section: Discussionmentioning
confidence: 99%